Making e-procurement work in a decentralized procurement system A comparison of three Indonesian cities - Achmad Nurmandi, Sunhyuk Kim (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to investigate the implementation of initiative e-procurement in decentralized system on Indonesia’s local government system